2012
DOI: 10.1016/s0019-4832(12)60002-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between peripheral arterial disease and coronary artery disease using ankle brachial index-a study in Indian population

Abstract: There is a definite and strong correlation between PAD and CAD. Correct diagnosis and supervision of patients with PAD is important for preventing the local progression of the disease and effective secondary prevention of future coronary and cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
5
30
1
Order By: Relevance
“…428). Nearly similar pattern of age distribution was reported by Sharmistha Sarangi, et al 28 in their study in India. This observation was being consistent with the findings of different studies done in foreign countries.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…428). Nearly similar pattern of age distribution was reported by Sharmistha Sarangi, et al 28 in their study in India. This observation was being consistent with the findings of different studies done in foreign countries.…”
Section: Discussionsupporting
confidence: 88%
“…In Asia the various studies showed the female patients formed a small percentage. [28][29][30][31][32] Except for higher prevalence of family history for ischemic heart disease in group I (p=0.003), other cardiovascular risk factors like hypertension (p=0.120), dyslipidemia (p=0.254) and obesity (0.093) were similarly in both group I and group II. The prevalence of risk factors in the present study was comparable with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly similar pattern of age distribution was reported by Sarangi S, et al 16 in their study in India. This observation was being consistent with the findings of different studies done in different countries [17][18][19] .…”
Section: Discussionsupporting
confidence: 88%
“…80% male and 15% female had coronary artery disease, which was statistically insignificant. 51.3% male and 0.0332% female had peripheral artery disease which was statistically significant (p=0.018) and OR=6.526 (95%CI for OR 1.252-34.029) Sarangi S, et al 16 and Al Thani, HA, et al 20 was found statistically significant.…”
Section: Discussionmentioning
confidence: 83%